Bibliometric Analysis of Coastal Poverty Research Trends for Sustainable Development - Nadofah Nadofah; Noer Aida Triandini; Ary Fauziah Amini (Buletin Ekonomika Pembangunan, 2025)
This study aims to comprehensively analyze research trends and themes related to coastal poverty, focusing on identifying dominant topics, shifts in research priorities, and existing knowledge gaps within the field. The novelty of this study lies in its longitudinal bibliometric approach, covering the period from 1949 to 2025, which provides a holistic understanding of how the discourse on coastal poverty has evolved over more than seven decades—an approach rarely explored in previous research. This study contributes to academic discussions by mapping the intellectual structure of coastal poverty studies, identifying areas for interdisciplinary collaboration, and supporting the formulation of future research agendas aligned with global sustainability goals. The research employs a bibliometric analysis using secondary data retrieved from the Scopus database, which were processed and visualized through VOS viewer software to analyze keyword co-occurrence, thematic clusters, and temporal research trends. The findings reveal that dominant themes in coastal poverty research include climate change, poverty, coastal areas, and sustainable development, with recent shifts toward food security, social vulnerability, and multidimensional poverty impacts. The study concludes that, despite the growing body of research, significant gaps remain in addressing issues of empowerment, equity, income, gender, and healthcare. Strengthening collaboration among researchers and institutions is crucial for promoting inclusive and sustainable development of coastal communities. Keywords: Coastal Poverty, Bibliometrics, Climate Change, Sustainable        Development